2015
DOI: 10.1021/jacs.5b07477
|View full text |Cite
|
Sign up to set email alerts
|

SSZ-13 Crystallization by Particle Attachment and Deterministic Pathways to Crystal Size Control

Abstract: Many synthetic and natural crystalline materials are either known or postulated to grow via nonclassical pathways involving the initial self-assembly of precursors that serve as putative growth units for crystallization. Elucidating the pathway(s) by which precursors attach to crystal surfaces and structurally rearrange (postattachment) to incorporate into the underlying crystalline lattice is an active and expanding area of research comprising many unanswered fundamental questions. Here, we examine the crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
199
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 209 publications
(213 citation statements)
references
References 76 publications
14
199
0
Order By: Relevance
“…Table lists the physicochemical properties of SSZ‐13‐T and SSZ‐13‐TF samples, in which both have the Si/Al ratio around 17, which is characteristic of zeolite SSZ‐13 . The BET surface area of SSZ‐13‐TF microspheres is 623 m 2 g −1 , indicating that the SSZ‐13‐TF microsphere particles were well crystallized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table lists the physicochemical properties of SSZ‐13‐T and SSZ‐13‐TF samples, in which both have the Si/Al ratio around 17, which is characteristic of zeolite SSZ‐13 . The BET surface area of SSZ‐13‐TF microspheres is 623 m 2 g −1 , indicating that the SSZ‐13‐TF microsphere particles were well crystallized.…”
Section: Resultsmentioning
confidence: 99%
“…Templated SSZ‐13 crystals (denoted as SSZ‐13‐T) were prepared using conventional hydrothermal methods similar to procedures described by Rimer and others, with a molar composition of 20 choline chloride:10 Na 2 O:2.6 Al 2 O 3 :100 SiO 2 :4400 H 2 O. Differently in this study, aluminum isopropoxide and choline chloride were used as aluminum source and organic template, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Often it is desirable to tune crystal size or introduce mesoporosity in Lewis acid zeolites to allow better diffusion to and from active sites and decrease the chance of pore blockage owing to deposition of side products. To this end, Rimer et al (30,31) have shown that zeolite growth modifiers are capable of modulating zeolite crystal structure. Ouyang et al (32) show that delaminated Sn-DZ-1, an MWW framework material with Sn postsynthetically incorporated into surface-accessible sites, has higher activity for the BV oxidation of 5-bromo-2-adamontanone with H 2 O 2 than Sn-Beta.…”
Section: Extended Propertiesmentioning
confidence: 99%
“…2a1). 21 Moreover, some nanorods with lengths in the micrometer scale are observed at the outer surface of those amorphous aggregates (Fig. 2a1, a2).…”
mentioning
confidence: 96%